(Un)Conventional Wisdom and Presidential Politics: The Myth of Convention Locations and Favorite-Son Vice Presidents. Issue 3 (15th July 2016) - Schultz, David
ABSTRACT: Conventional wisdom pervades presidential politics, and there is no doubt that this will again be true in 2016. First among "old politicians' tales" is that a political party's placement of a national convention in a specific state can affect presidential voting there, swinging or flipping it to its presidential candidate. Second, the selection of a vice-presidential candidate as a favorite son (or daughter) will deliver a state's electoral votes to a presidential ticket. Is either of these pearls of wisdom true? This article tests the truth of both the convention location and favorite-son claims and finds little evidence of their efficacy.